Determinants and Effects of School Age Childcare on Children’s Cognitive and Socio-Emotional Outcomes at Age 13 - Byrne, Delma (The Economic and Social Review, 2016)
Little is known about the determinants or the influence of childcare arrangements for school age children in the Irish context. Using longitudinal data from Wave 1 and Wave 2 of the Growing Up in Ireland (GUI) child cohort study, this paper examines the factors associated with participation in non-parental after-school care in middle childhood and examines the influence of such care settings on children’s outcomes at age 13. The findings show that participation in the type of after-school clubs captured by the GUI data (largely paid care in a group setting) is supporting children with specific educational needs and those with limited family support, as well as being strongly associated with maternal employment and high household income. Cognitive and socio-emotional outcomes at thirteen years are best explained by child, family, school and parental characteristics rather than direct effects of the type of out-of-school care arrangement held at age nine.